Sound: production, perception, hearing loss & treatment options - Bibi Kulsoom; Nasim Karim (Journal of the Pakistan Medical Association, 2022)
Sound is an important communication tool for humans that contain information about the surrounding environment. It may signify a danger or a reward for an organism. In humans, the mechanism of sound production and perception is complex and sophisticated. Sound is produced by vibrating body in a medium that contains molecules in the surrounding space. The sound perception starts in human foetus at around the third trimester where it plays a vital role in organising the foetal brain. This process continues after birth and can be exploited by various endogenous and exogenous factors. Many mechanisms that can modulate hearing process at different levels lead to subclinical or clinical presentation of hearing-related problems. It is important to contemplate the mechanisms underlying sound production, perception and pathogenesis of hearing loss. This will facilitate prescribing a relevant treatment option according to the cause and its underlying mechanism. –Continue